Wingate test peak power is positively correlated to peak torque and power in bilateral isokinetic knee dynamometry - Lunn, William R; Zenoni, Maria; Crandall, Ian; Berglund, Michelle; Dress, Ashley; Wiley, Charlie; Axtell, Robert S (The FASEB Journal, 2011)
Citation Key Alias: lens.org/159-510-863-665-515 tex.type: [object Object]
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

A Prediction Of Vo2peak: Least Intrusive Model In Males 18-35 Years: 2325: Board #202 June 2 3:30 PM - 5:00 PM. - Crandall, Ian; Finn, Joan; Latchman, Peter; Thiel, Robert; Mugno, Raymond; Zenoni, Maria; Sollanek, Kurt; Axtell, Robert (Medicine & Science in Sports & Exercise, 2011)
0 citations (Crossref) [2023-10-31] Place: (C) 2011 American College of Sports Medicine
Keywords: dept.hms; dept.mat

Effect of hospitalizations on physical activity patterns in mobility-limited older adults - Wanigatunga, Amal A.; Gill, Thomas M.; Marsh, Anthony P.; Hsu, Fang-Chi; Yaghjyan, Lusine; Woods, Adam J.; Glynn, Nancy W.; King, Abby C.; Newton, Jr., Robert L.; Fielding, Roger A.; Pahor, Marco; Manini, Todd M.; et al. (Journal of the American Geriatrics Society, 2019)
OBJECTIVES: To evaluate the effect of hospitalizations on patterns of sedentary and physical activity time in mobility-limited older adults randomized to structured physical activity or health education. DESIGN: Secondary analysis of investigator-blinded, parallel-group, randomized trial conducted at 8 U.S. centers between February 2010 and December 2013. PARTICIPANTS: Sedentary men and women aged 70 to 89 at baseline who wore a hip-fitted accelerometer 7 consecutive days at baseline and 6, 12, and 24 months after randomization (N=1,341). MEASUREMENTS: Participants were randomized to a physical activity (PA; n = 669) intervention that included aerobic, resistance, and flexibility training or to a health education (HE; n = 672) intervention that consisted of workshops on older adult health and light upper-extremity stretching. Accelerometer patterns were characterized as bouts of sedentary (¡100 counts/min; ¿= 1, ¿= 10, ¿= 30, ¿= 60 minute lengths) and activity (¿= 100 counts/min; ¿= 1, ¿= 2, ¿= 5, ¿= 10 minute lengths) time. Each participant was categorized as having 0, 1 to 3, or 4 or more cumulative hospital days before each accelerometer assessment. RESULTS: Hospitalization increased sedentary time similarly in both intervention groups (8 min/d for 1-3 cumulative hospital days and 16 min/d for ¿= 4 cumulative hospital days). Hospitalization was also associated with less physical activity time across all bouts of less than 10 minutes (¿= 1: -7 min/d for 1-3 cumulative hospital days, -16 min/d for ¿= 4 cumulative hospital days; ¿= 2: -5 min/d for 1-3 cumulative hospital days, -11 min/d for ¿= 4 cumulative hospital days; ¿= 5: -3 min/d for 1-3 cumulative hospital days, -4 min/d for ¿= 4 cumulative hospital days). There was no evidence of recovery to prehospitalization levels (time effect p ¿ .41). PA participants had less sedentary time in bouts of less than 30 minutes than HE participants (-8 to -10 min/d) and more total activity (+3 to +6 min/d), although hospital-related changes were similar between the intervention groups (interaction effect p ¿ .26). CONCLUSION: Participating in a PA intervention before hospitalization had expected benefits, but participants remained susceptible to hospitalization's detrimental effects on their daily activity levels. There was no evidence of better activity recovery after hospitalization.
15 citations (Crossref) [2023-10-31] tex.eissn: 1532-5415 tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Newton, Robert/0000-0002-6863-913X Wanigatunga, Amal/0000-0002-5763-5184 Gill, Thomas/0000-0002-6450-0368 Glynn, Nancy/0000-0003-2265-0162 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 tex.unique-id: ISI:000459714900011
Keywords: accelerometer; clinical trial; dept.hms; exercise; hospital; peer-reviewed; sedentary behavior